Vanishing of room-temperature slip avalanches in a face-centered-cubic high-entropy alloy by ultrafine grain formation. (October 2018) - Qiang, Jian; Tsuchiya, Koichi; Diao, Haoyan; Liaw, Peter K.
Abstract: High-pressure torsion (HPT) was applied to Al0.3 CrFeCoNi high-entropy alloy to study the effect of severe grain-refinement on the deformation behavior. After 10 rotations of HPT, the grain size was reduced to tens of nanometers. Nano-twins and stacking faults were found in the nano-grained samples. This nano-grain formation led to an obvious increase in micro-Vickers hardness, and vanishing of slip avalanches during nanoindentation which was evidenced by the absence of pop-ins in the loading segment. These phenomena can be attributed to the affluent grain boundaries that acted as extra mediators for plastic deformation and obstacles for the propagation of lattice dislocations. Graphical abstract: Unlabelled Image